Nursing report on the combination of auricular acupoint comprehensive therapy and guided music imagination technology to improve fatigue symptoms in a patient with decompensated liver cirrhosis (耳穴"三序"疗法联合引导性音乐想象技术改善1例肝硬化失代偿期患者疲乏症状群的护理体会) - LIAN Xiaojing (廉晓静); YANG Xinghua (杨兴华); HUANG Yanping (黄砚萍); TIAN Xiaodong (田小冬) (Journal of International Translational Medicine Limited, 2024)
This article summarizes nursing practice of a patient with decompensated liver cirrhosis (liver depression and spleen deficiency type) who received comprehensive auricular acupoint therapy combined with guided music imagination technology to improve fatigue symptoms. Based on the comprehensive evaluation on primary symptoms of the patient, auricular acupoint massage, scraping, and pressing therapy at the appropriate time, combined with guided imagination techniques, were carried out to alleviate the severity of symptoms such as fatigue, sleep quality, and anxiety of the patient, improve overall quality of life and overall therapeutic effect, and provide clinical basis for clinical nursing. (本文总结1例耳穴"三序"疗法联合引导性音乐想象技术改善肝硬化失代偿期(肝郁脾虚型)患者疲乏症状群的护理经验。入院后完善护理评估, 基于患者主要症状, 采用耳穴按摩、耳部刮痧、耳穴贴压"三序"疗法联合引导性音乐想象技术进行干预, 缓解患者疲乏、焦虑、失眠症状, 提高其总体生活质量。)